17. MELANOMA BRAIN METASTASIS: PRESENTATION, TREATMENT AND OUTCOMES IN THE AGE OF TARGETED- AND IMMUNO-THERAPIES. (4th August 2020) - Bander, Evan D; Yuan, Melissa; Carnevale, Joseph A; Reiner, Anne S; Panageas, Katherine S; Postow, Michael A; Tabar, Viviane; Moss, Nelson S
Abstract: BACKGROUND: Melanoma brain metastasis (MBM) prognosis has historically been dismal. However, breakthroughs in targeted and immunotherapies have improved long-term survival in advanced melanoma. As such, MBM presentation, prognosis and multimodality CNS-directed treatment use were reassessed in this contemporary age of treatment. METHODS: This retrospective study evaluated patients treated at Memorial Sloan Kettering Cancer Center between 2010–2019 with a diagnosis of melanoma brain metastases (MBM). Kaplan-Meier methodology was used to describe overall survival (OS). Recursive partitioning analysis (RPA) and time-dependent multivariable Cox modeling were used to assess prognostic variables and associate CNS-directed treatments with OS. RESULTS: Four hundred and twenty-five patients with 2, 488 MBM were included. Median OS from MBM diagnosis was 8.9 months (95%CI: 7.9–11.3). RPA demonstrated significantly longer survival in patients diagnosed with MBM between 2015–2019 versus 2010–2014 (13.0 months [95%CI: 10.47–17.06] versus 7.0 months [95%CI: 6.1–8.3]; p=0.0003) and patients with <5 BM versus ≥5 BM (12.49 months [95%CI: 10.52–16.03] versus 5.48 months [95%CI: 4.2–6.8]; p<0.0001). Prognostic multivariable modeling significantly associated shortened OS independently with leptomeningeal dissemination (p<0.0001), >5 BM at diagnosis (p<0.0001), MBM diagnosis year 2010–2014 (p=0.0007), immunotherapy treatment prior to BM diagnosis (p=0.02), and extracranial disease presence (p=0.03). CNS-directed treatment modalities associated with BM number, dominant BM size, presenting symptoms, diagnosis year, and extracranial disease presence. Multivariable analysis demonstrated improved survival for patients that underwent craniotomy (p=0.01). CONCLUSIONS: MBM prognosis has improved in the period following targeted and immunotherapy introduction, and even within the last 5 years of this study. Improving survival reflects and may influence the willingness to use aggressive multimodality treatment for MBM.